Changes in the thermal, pasting, morphological and structural characteristic of common buckwheat starch after ultrafine milling. (30th November 2020) - Huang, Yawei; Sun, Xiangxiang; Guo, Hongmei; He, Xueshu; Jiang, Jiang; Zhang, Guoquan; Li, Wenhao
Summary: The effects of superfine milling treatments on the thermal, pasting, morphological and structural characteristics of common buckwheat starch were studied. The results showed that the superfine milling could change the morphological structure of buckwheat starch granules. Superfine milling treatments decreased the relative crystallinity and destroyed crystal particles of buckwheat starch. The crystallinity of buckwheat starch was 0.00% after 4 h of the ultrafine milling treatment. There is no obvious endothermic melting peak in the buckwheat starch after ultrafine milling treatment. After superfine milling, the light transmittance, swelling power and solubility of buckwheat starch increased, while PV, TV and FV values decreased. Superfine milling could significantly improve the WHC value of buckwheat starch. This study is expected to obtain the modified buckwheat starch with improved properties and provide valuable information for starch modification employing extreme milling, as well as provide the theoretical basis for expanding the application of buckwheat starch.